A new type of nano open set - Shareef, Hardi A.; Aziz, Hardi N.; Hamakarim, Hilal O. (Sulaimani Journal for Pure and Applied Sciences, 2022)
The objective of this work is to introduce a new class of nano open set called nano 𝑆𝑤- open set in nano topological spaces. Basic properties of nano 𝑆𝑤-open sets are analyzed and compare this nano set with some other nano open sets.
Keywords: Nano 𝑆𝑤open set; Nano semiopen set; Nano topological space